충남분지 성주리향사의 구조기하학적 해석 - 노정래(Jungrae Noh); 박승익(Seung-Ik Park); 권상훈(Sanghoon Kwon) (자원환경지질, 2018)
Chungnam Basin has been known as one of the largest Mesozoic basins in Korea, filled mainly with so-called Daedong Supergroup. The basin has evolved as the Early to Middle Jurassic intra-arc volcano-sedimentary basin developed on top of the Late Triassic to Early Jurassic post-collisional basin in this area, recording evolutionary history of the Mesozoic tectonics in the southwestern Korean Peninsula. This study carries out the geometric interpretations of the Seongjuri syncline and its surroundings in the central part of the Chungnam Basin, based on detailed structural field survey. Based on its doubly-plunging fold geometry, the Seongjuri syncline could be subdivided into the southwestern and northeastern domains. On the down-plunge profiles of the southwestern domain of the Seongjuri syncline as well as the underlying Okma fold, the Okma fault shows typical geometry of a basement-involved reverse fault that propagated up to the sedimentary cover. The profiles illustrate that the Seongjuri syncline occurs in front of the tip of the Okma fault, likely implying its origin as a part of the fault-related fold system. The result of this study will provide better insight into the structural interpretation of the Chungnam Basin, and will further provide useful information for the Mesozoic orgenic events of the southwestern Korean Peninsula. 후기 트라이아스기~전기 쥬라기의 후 충돌 분지 상위에 전기 및 중기 쥬라기의 호 내부 분지가 중첩되어 나타나는 충남분지는 대동누층군의 분포 지역으로 잘 알려져 있으며, 중생대 퇴적분지의 진화와 지구조 운동과의 상관관계를 규명하는데 매우 중요한 지역이다. 본 연구에서는 충남분지에 발달하고 있는 지질구조 연구의 일환으로서 분지 중앙부에 위치하는 성주리향사 및 주변 지역에 대한 지표 지질조사를 통해 구조기하학적 해석을 수행하였다. 연구지역에 발달하는 대표적인 지질구조로는 성주리향사와 더불어 옥마단층, 옥마습곡, 백운사단층이 있다. 연구의 대상인 성주리향사는 층리 자세의 변화에 따라 크게 남서부 및 북동부의 두 영역으로 나뉘며, 각 영역의 힌지가 저점으로 모이는 이중침강습곡의 형태를 보인다. 성주리향사 남서부 및 옥마습곡에 대한 하향 투영을 통해 작성된 단면을 해석한 결과, 옥마단층 및 옥마습곡은 기반암 내의 단층이 상위의 퇴적암으로 전파하면서 발달한 구조로 판단되며, 성주리향사는 옥마단층의 단층말단 상부에 형성된 배사 및 향사의 일부로 해석된다. 본 연구의 결과는 충남분지 및 더 나아가 중생대 조산대로서 한반도 남서부에 기록되어 있는 변형사를 밝히는 데에 유용하게 활용될 수 있을 것으로 생각된다.